Sistem Pakar Diagnosa Kerusakan Printer Menggunakan Metode Teorema Bayes - Ellisa Harini; Indra Tri Saputra; Gusmana, Roman (Journal of Big Data Analytic and Artificial Intelligence, 2023)
Trijaya Computer performs computer sales and repair services located on Jl. Panglima Batur, Markoni. Printer repair demands quite a lot. Its massive usage is for printing reports, documents, and other things. Extensive use or even non-use of the printer can damage it. The research applies Bayes' Theorem analysis to an expert system to help admins diagnose printer damage. The discoverer of Theorem by Reverend Thomas Bayes (1701-1761). In general, it is to calculate the probability truth value of evidence. It can also interpret to calculate data uncertainty into definitive data by comparing "yes" or "no" data. The study result was an expert system for diagnosing printer damage as a support system or admins assistant with 80% accuracy. Eight of ten test data were equal to the expert's result.